CULINARY BUSINESS OF FRESHWATER FISH RESTAURANT IN TANJUANG ANAU, OMPANG TANAH SIRAH VILLAGE, PAYAKUMBUH CITY, WEST SUMATERA PROVINCE ( CASE STUDY IN RESTAURANT TELUR IKAN MIS ) - Vella Vintari; Hendrik Hendrik; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTResearch on culinary business restaurant “Telur Ikan Mis” was conducted in july 2019, aims to determine variations in menu, visitor characteristics, production costs, income and profits frome culinary business. The metode used in this research is survey method. Respondents in this study were business owner, 5 employees, 80 visitors. The results of this study show that there are 19 menu variations offered, associated with fish as many as 14 kinds of menus, chiken and meet as much as 5 kinds of menu. The menu is the most from fish, while of all there are specific menus, namely fish eggs. Visitors who come have an age range of 15-60 years. Most of the visitors came from payakumbuh with a precentage of 70% and 30% from other regions. The average monthly imcome is IDR 312.000.000, The average monthly production cost is IDR 283.438.626. Keywords : culinary business, fish egg, menu variations, spesific food, freshwater fish